Electrochemical advanced oxidation processes using novel electrode materials for mineralization and biodegradability enhancement of nanofiltration concentrate of landfill leachates. (1st October 2019) - El Kateb, Marwa; Trellu, Clément; Darwich, Alaa; Rivallin, Matthieu; Bechelany, Mikhael; Nagarajan, Sakthivel; Lacour, Stella; Bellakhal, Nizar; Lesage, Geoffroy; Héran, Marc; Cretin, Marc
Abstract: The objective of this study was to implement electrochemical advanced oxidation processes (EAOPs) for mineralization and biodegradability enhancement of nanofiltration (NF) concentrate from landfill leachate initially pre-treated in a membrane bioreactor (MBR). Raw carbon felt (CF) or Fe II Fe III layered double hydroxides-modified CF were used for comparing the efficiency of homogeneous and heterogeneous electro-Fenton (EF), respectively. The highest mineralization rate was obtained by heterogeneous EF: 96% removal of dissolved organic carbon (DOC) was achieved after 8 h of electrolysis at circumneutral initial pH (pH0  = 7.9) and at 8.3 mA cm −2 . However, the most efficient treatment strategy appeared to be heterogeneous EF at 4.2 mA cm −2 combined with anodic oxidation using Ti4 O7 anode (energy consumption = 0.11 kWh g −1 of DOC removed). Respirometric analyses under similar conditions than in the real MBR emphasized the possibility to recirculate the NF retentate towards the MBR after partial mineralization by EAOPs in order to remove the residual biodegradable by-products and improve the global cost effectiveness of the process. Further analyses were also performed in order to better understand the fate of organic and inorganic species during the treatment, including acute toxicity tests (Microtox ® ), characterization of dissolved organic matter by three-dimensional fluorescence spectroscopy, evolution of inorganic ions (ClO3 −, NH4 + and NO3 − ) and identification/quantification of degradation by-products such as carboxylic acids. The obtained results emphasized the interdependence between the MBR process and EAOPs in a combined treatment strategy. Improving the retention in the MBR of colloidal proteins would improve the effectiveness of EAOPs because such compounds were identified as the most refractory. Enhanced nitrification would be also required in the MBR because of the release of NH4 + from mineralization of refractory organic nitrogen during EAOPs. Graphical abstract: Image 1 Highlights: NF concentrate of landfill leachate pre-treated in a membrane bioreactor was treated. Ti4 O7 anode and Fe II /Fe III LDH-CF cathode was used for the first time for a real effluent. 96% removal of dissolved organic carbon was achieved by heterogeneous electro-Fenton. Optimal conditions for biodegradability enhancement were identified. Optimal conditions for minimization of toxic by-products were identified.